MENOPAUSAL TRANSITION AMONG NORTHERN INDIAN WOMEN - S., Vijayalakshmi; Chandrababu, Ramesh; L., Eilean Victoria (Journal of Health and Allied Sciences NU, 2013)
According to Indian menopause society research there are about 65 million Indian women over the age of 45. Average age of menopause in around 48 yrs but it strikes Indian women as young as 30-35 years.The main aim of the study is to assess the menopausal transition among women residing at selected rural community, Punjab. The study was conducted from July 2012 to December 2012.The sample from the selected rural community and the research design used for this study was Non experimental design – descriptive survey method. The sample size selected for this study consists of 30 rural women 40-55 years of age from selected rural community at Amritsar. Purposive sampling method was used to select the samples. The tool used in this study was ZEG Berlin menopause rating scale to assess the menopausal transition. The data analysis was done using both descriptive and inferential statistics.The results reported that more prevalent symptoms were feeling tired (92.90%), headache (88.80%), joint and muscular discomfort (76.20%), physical and mental exhaustion (60.09%), sleeplessness (54.40%), depressive mood (37.30%), irritability (36%), dryness of vagina (36%), hot flushes and sweating (35.80%) and anxiety (34.50%).The rural women of Amritsar, Punjab experience high prevalence of menopausal symptoms. The high percentage and scores of MRS were observed in perimenopausal and postmenopausal women.
Keywords: Menopausal Transition; Rural Community Women; Northern India